Graph-Root: Prediction of Root-Associated Proteins in Maize, Sorghum, And Soybean Based on Graph Convolutional Network and Network Embedding Method - Zhou, Bo; Liu, Siyang; Chen, Lei; Dai, Qi (Current Bioinformatics, 2025)
BackgroundThe root system plays an irreplaceable role in plant growth. Its improvement can increase crop productivity. However, such a system is still mysterious for us. The underlying mechanism has not been fully uncovered. The investigation on proteins related to the root system is an important means to complete this task. In the previous time, lack of root-related proteins makes it impossible to adopt machine learning methods for designing efficient models for the discovery of novel root-related proteins. Recently, a public database on root-related proteins was set up and machine learning methods can be applied in this field.ObjectiveThe purpose of this study was to design an efficient computational method to predict root-associated proteins in three plants: maize, sorghum, and soybean.MethodsIn this study, we proposed a machine learning based model, named Graph-Root, for the identification of root-related proteins in maize, sorghum, and soybean. The features derived from protein sequences, functional domains, and one network were extracted, where the first type of features were processed by graph convolutional neural network and multi-head attention, the second type of features reflected the essential functions of proteins, and the third type of features abstracted the linkage between proteins. These features were fed into the fully connected layer to make predictions.ResultsThe 5-fold cross-validation and independent tests suggested its acceptable performance. It also outperformed the only previous model, SVM-Root. Furthermore, the importance of each feature type and component in the proposed model was investigated.ConclusionGraph-Root had a good performance and can be a useful tool to identify novel root-related proteins. BLOSUM62 features were found to be important in determining root-related proteins.
Keywords: Root-related proteins